PEMBELAJARAN TARI SIGEH PENGUTEN DALAM KEGIATAN EKSTRAKURIKULER DI SMA PERINTIS 2 BANDAR LAMPUNG - Ariyadi Ariyadi; Munaris Munaris; I Wayan Mustika (Jurnal Seni dan Pembelajaran, 2015)
The problem in this research was how the process and outcomes of sigeh penguten dance in extracurricular activities in SMA Perintis 2 Bandar Lampung. The theory used was the theory of learning. This type of research was qualitative descriptive. Source of the data obtained in this study were dance teachers, 7 students and range of motion sigeh penguten dance. Data collection techniques used were observation, interviews, documentation and practices testing. Learning was held in eight meetings, teachers used three methods, namely modeling, demonstrations, and exercises. In modeling process, the teacher becomes a model to demonstrate the dance movement. Demonstration after teacher did the modeling process and students followed together, and did the exercises was each student dance the sigeh penguten dance together. Assessment was given through three aspects: movement technique, memorization, and expression. Learning outcomes of sigeh penguten dance in extracurricular activities are